Drug treatment of toxoplasmic encephalitis in acquired immunodeficiency syndrome. Issue 837 (July 1995) - Winstanley, P.
Abstract : Toxoplasma gondii is a ubiquitous parasite, which causes several serious diseases. Until the AIDS pandemic, toxoplasmic encephalitis was largely confined to the pharmacologically immune-suppressed and to cases of congenital transmission. T gondii is now one of the more commonly encountered opportunistic pathogens of advanced AIDS.